SEMA BINDING STRENGTH NO. 2/2023 REGARDING THE JUDGE'S DETERMINATION IN APPLICATIONS FOR REGISTRATION OF INTERFAITH MARRIAGES - Leonide, Cliff Ivan; Khoidin, M.; Zulaika, Emi; Poesoko, Herowati; Suci, Ivida Dewi Amrih (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The state guarantees freedom of religion, as well as forming a marriage. Registration of marriages, especially mixed marriages, is regulated in Article 57 of Law no. 16 of 2019 concerning Marriage. This mixed marriage is also related to interfaith marriage which is also a right for Indonesian citizens. The Supreme Court in this case made SEMA No. 2/2023 dated 17 July 2023 concerning Appointments for Judges in Adjudicating Cases on Applications for Registration of Marriages Between People of Different Religions and Beliefs, at point No. 2 explains that